PERCOBAAN PENGISIAN-PENGELUARAN HIDROGEN SEBUAH TANGKI SIMPAN HIDROGEN PADAT - Suwarno, Hadi (Jurnal Metalurgi, 2012)
Storing hydrogen in the form of metal-hydride is one of the most promising fuels for transport vehicles because of its high gravimetric density. A solid hydrogen storage tank with the volume of tank about one liter containing about 700 g of nano powders Mg2Ti5Fe6 alloy has been fabricated for performing the hydrogen charging-discharging cycles. Charging-discharging of hydrogen into/out from the tank is conducted at room temperature at the varied pressure of 2, 6.5 and 8 bars. It is exhibited that the ratio of hydrogen capacity of the tank containing Mg2Ti5Fe6 nano particle to the empty tank is 1.3, 2.3, and 2.8, respectively. Charging experiment at higher pressure could not be conducted due to the limit of facility. It is predicted that at higher pressure the hydrogen capacity of the tank will be increased. From the experimental results it is concluded that the preliminary study on charging-discharging solid state hydrogen has been done successfully. Further examination in the form of its application in the fuel cell is being scheduled.